MicroRNA‐155 Regulates ROS Production, NO Generation, Apoptosis and Multiple Functions of Human Brain Microvessel Endothelial Cells Under Physiological and Pathological Conditions. Issue 12 (8th October 2015) - Liu, Yajing; Pan, Qunwen; Zhao, Yuhui; He, Caixia; Bi, Kexia; Chen, Yusen; Zhao, Bin; Chen, Yanfang; Ma, Xiaotang
ABSTRACT The microRNA‐155 (miR155) regulates various functions of cells. Dysfunction or injury of endothelial cells (ECs) plays an important role in the pathogenesis of various vascular diseases. In this study, we investigated the role and potential mechanisms of miR155 in human brain microvessel endothelial cells (HBMECs) under physiological and pathological conditions. We detected the effects of miR155 silencing on ROS production, NO generation, apoptosis and functions of HBMECs at basal and in response to oxidized low density lipoprotein (ox‐LDL). Western blot and q‐PCR were used for analyzing the gene expression of epidermal growth factor receptor (EGFR)/extracellular regulated protein kinases (ERK)/p38 mitogen‐activated protein kinase (p38 MAPK), phosphatidylinositol‐3‐kinase (PI3K) and serine/threonine kinase(Akt), activated caspase‐3, and intercellular adhesion molecule‐1 (ICAM‐1). Results showed that under both basal and challenge situations: (1) Silencing of miR155 decreased apoptosis and reactive oxygen species (ROS) production of HBMECs, whereas, promoted nitric oxide (NO) generation. (2) Silencing of miR155 increased the proliferation, migration, and tube formation ability of HBMECs, while decreased cell adhesion ability. (3) Gene expression analyses showed that EGFR/ERK/p38 MAPK and PI3K/Akt were increased and that activated caspase‐3 and ICAM‐1 mRNA were decreased after knockdown of miR155. In conclusion, knockdown of miR155 could modulate ROS production, NO generation, apoptosis and function of HBMECs via regulating diverse gene expression, such as caspase‐3, ICAM‐1 and EGFR/ERK/p38 MAPK and PI3K/Akt pathways. J. Cell. Biochem. 116: 2870–2881, 2015. © 2015 Wiley Periodicals, Inc.